(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article talks about the fact that Kashkadarya is a holy place of pilgrimage and a land rich in temples. The author clarified the problem on the basis of existing scientific literature, relying on historical data and archival sources. Comparative analysis of existing unique approaches and theories regarding the fact that Kashkadarya is a holy place of pilgrimage and a land rich in monuments.